Lessons from U.S. allies in security cooperation with third countries the cases of Australia, France, and the United Kingdom - Moroney, Jennifer D. P., 1973- (Technical report (Rand Corporation), 2011)
Like the U.S. Air Force, many U.S. allies work with partner countries on security matters, sometimes even with the same partners, but on a smaller scale. But how, where, and why do these allies engage the same countries? Would working together in particular areas be worthwhile or viable and can specific lessons be learned from their experiences, for example, in the areas of planning, resourcing and assessments? This report explores these questions by examining both the positive aspects and the challenges of the security cooperation approaches of three U.S. allies, Australia, France, and the United Kingdom. These three capable allies are experienced in working with civilian counterparts and benefit from higher-level departmental guidance. They generally do so with relatively small budgets, leading them to learn to economize, pool resources, and take advantage of joint and interagency planning. These strategies can inform current U.S. thinking on security cooperation. They also suggest venues for further collaboration between allies, particularly in the three key areas of staff talks, exercises, and training followed by exercises --